Shifting Roles and Political Support of Kiai Individual, Structure, and Integrative Perspectives - SUSWANTA, SUSWANTA (Universitas Muhammadiyah Yogyakarta, 2014)
The study establishes the individual of kiai as a determinant autonomous actor of shifting roles and political support ‘ assume ‘ that the problem of shifting roles and political support of kiai are problems related to the quality of the individual ( individual quality) kiai alone. While studies that put the structure as an autonomous actor explaining that problem of shift in the role and political support of kiai turns laced with systems or structures that surround the life of kiai. Kiai is no longer a mere accused or suspect. Compared with the two previous perspectives, the study which makes a link of kiai and structure as a determinant actor of crisis of political agency of kiai or shifting political roles of kiai from cultural broker to political broker either to political player in the reform era is look more able to explain the problem in a comprehensive manner. The explanation which is given is also open awareness that the problem of shifting political roles or crisis of political agency of kiai in the reform era was not only related to the quality of the kiai alone, but also by the growing structure and surrounding kiai life. Keyword: Roles and Political Support, Kiai, Individual and Structure